The Influence of Perceived Benefits, Financial Literacy, and Demographics on Health Insurance Purchase Intention by Gen Z Which is Mediated by Attitude - Darwin Darwin; Kurnadi Gularso (PT. Publikasiku Academic Solution, 2024)
The insurance penetration rate in Indonesia remains low and has even been declining, despite the significant role the insurance industry plays in supporting national development. Meanwhile, Generation Z is beginning to dominate Indonesia's demographic structure, particularly as the demographic bonus period approaches. Low financial literacy is often cited as a cause of the low attitude and purchase intention towards life insurance. Additionally, low perceived benefit of insurance is also known to influence Generation Z's attitude. Generation Z is also associated with behaviors that differ from previous generations. This study aims to identify the factors influencing Generation Z's attitude and purchase intention towards life insurance, focusing on financial literacy, perceived benefit, and demographics. The research method is quantitative, with samples taken from Generation Z residents in Jabodetabek who have income but do not yet have life insurance. The research instrument used is a questionnaire, with a total of 297 valid questionnaires collected and analyzed using variance-based structural equation modeling (SEM). The results show that financial literacy, perceived benefit, and demographics have a significant and positive influence on Generation Z's attitude and purchase intention. Among these factors, perceived benefit emerges as the strongest predictor of attitudes towards life insurance. The financial literacy level of Generation Z in Jabodetabek is found to be adequate. This indicates that financial literacy does not directly translate into insurance literacy, suggesting that financial literacy is not the main cause of the low attitude and purchase intention towards life insurance among Generation Z in Indonesia.